أثر إجمالي التكوين الرأسمالي الثابت وعرض النقد على النشاط الاقتصادي (تحليل سلاسل زمنية) (Latakia University Journal - Economic and Legal Sciences Series, 2019)
The main aim of this study is to investigate the effects of gross fixed capital formation and money supply on economic activity in Algeria over the period 1971-2003.To achieve this objective, a time series analysis technique has been applied to the three major variables of the study: gross fixed capital formation (GFCF), the narrow definition of money supply (M), and finally the gross domestic product (GDP) to stand as an indicator of economic activity. The results have, in general, found that gross fixed capital formation has a stronger effect on real gross domestic product than money supply. This implies that the Algerian government should focus on the level of investment rather than on monetary policy to stimulate economic growth. تهدف هذه الدراسة بشكل أساسي إلى استقصاء أثر كل من إجمالي التكوين الرأسمالي الثابت وعرض النقد على النشاط الاقتصادي في الجزائر خلال الفترة الزمنية (1971-2003). ولتحقيق هذا الهدف تم تطبيق أسلوب تحليل السلاسل الزمنية على المتغيرات الرئيسية في الدراسة وهي: إجمالي التكوين الرأسمالي الثابت، عرض النقد، والناتج المحلي الإجمالي كمتغير ممثل للنشاط الاقتصادي. وبشكل عام، بينّت نتائج الدراسة بأن أثر إجمالي التكوين الرأسمالي الثابت يفوق أثر عرض النقد على النشاط الاقتصادي في الجزائر. وهذا يتضمن بأنه على الحكومة الجزائرية التركيز على الجانب الاستثماري لحفز النشاط الاقتصادي الجزائري.